Effective Dosing of Topotecan with Carboplatin in Relapsed Ovarian Cancer (TAJ: Journal of Teachers Association, 2018)
Patients and Methods: Topotecan was given as a 30-minute infusion daily for 5 days, with carboplatin given immediately after topotecan on day 5. Treatment was repeated every 21 days. Carboplatin and then topotecan were escalated in sequential cohorts of three to six patients. Four dosage combinations of topotecan days 1 to 5 and carboplatin (day 5) were tested: 0.5 mg/m2/d and carboplatin area under the curve (AUC) of 4, topotecan 0.5 mg/m2/d and carboplatin AUC of 5, topotecan 0.75 mg/m2/d and carboplatin AUC of 5, and topotecan 1.0 mg/m2/d and carboplatin AUC of 5.Results: Grade 3 and 4 neutropenia was common at doses of 0.75 mg/m2/d and above, but dose-limiting hematologic toxicity occurred in only one patient. The most common reason for dose reduction or delay was failure of myelosuppression to resolve by day 21. Nonhematologic toxicity was generally mild. The maximum-tolerated dose as defined in the protocol was not reached, but topotecan dose escalation was stopped at 1.0 mg/m2/d, because delayed neutrophil recovery precluded re-treatment on a 21-day schedule.Conclusion: Hematologic toxicity was common but rarely serious, and the combination of topotecan with carboplatin on this schedule was safe and well tolerated. Giving carboplatin to patients after topotecan on day 5, rather than on day 1, allowed dose escalation beyond the levels reported in other studies. The recommended doses for previously treated patients are topotecan 0.75 mg/m2/d, days 1 to 5, with carboplatin at an area under the curve (AUC) of 5 following topotecan on day 5. The combination of topotecan 1 mg/m2/d, days 1 to 5, followed on day 5 by carboplatin at an AUC of 5, merits further examination in untreated patients.TAJ 2016; 29(2): 31-36